Associated Injuries in Patients with Traumatic Spinal Cord Injury - Mas, Manuel F.; Quintana, José; Blanco, Anna; Deya, Javier; Frontera, Natasha L.; Latimer, Marcos R.; Pérez, Félix; Conde, José G.; Frontera, Walter R. (Puerto Rico Health Sciences Journal, 2025)
Objective: This cross-sectional study assessed the type and frequency of injuries associated with traumatic spinal cord injury (TSCI). Methods: The NTRACS Hospital Trauma Registry database of the Puerto Rico Trauma Hospital was reviewed for the medical records of all admissions with the International Classification of Diseases, 10th Revision, Clinical Modification codes S12–S14, S22–S24, and S32–S34 for the years 2019 through 2022. The injury characteristics recorded included neurological level, mechanism, severity score, hospital length of stay, and associated injuries. Results: The median number of associated injuries per TSCI patient was 5, and 136 TSCI patients (93.8%) had more than 1 injury. Common injury diagnostic code groups included fractures of the ribs, sternum, and thoracic spine; injuries to intrathoracic organs; fractures of the cervical vertebra and neck; and fractures of the lumbar spine and pelvis. Notably, 88.3% of the TSCI patients had at least 1 injury that could complicate rehabilitation, with one-third having upper extremity fractures and 1 in 5 having a concurrent traumatic brain injury. There was a weak positive correlation between length of stay and the number of associated injuries, as well as with the injury severity score. Conclusion: These findings indicate that associated injuries are prevalent in TSCI patients, potentially complicating acute care and patient outcomes. A consensus definition of associated injuries in TSCI—particularly those that can complicate rehabilitation—is needed.